Evaluation of Extra-High Translucent Dental Zirconia: Translucency, Crystalline Phase, Mechanical Properties, and Microstructures - Hiroto Nakai; Masanao Inokoshi; Hengyi Liu; Motohiro Uo; Manabu Kanazawa (Journal of Functional Biomaterials)
Highly translucent zirconia (TZ) is frequently used in dentistry. The properties of several highly translucent zirconia materials available in the market require an in-depth understanding. In this study, we assessed the translucency, crystalline phase, mechanical properties, and microstructures of three newly developed highly translucent zirconia materials (Zpex 4. m, 4 mol% yttria-stabilized zirconia: 4YSZ; Zpex Smile.m, 5YSZ; ZR Lucent ULTRA, 6YSZ). The translucency parameter (TP) was analyzed using the CIELAB system. X-ray diffraction was conducted for the crystalline phase analysis, followed by Rietveld refinement. A biaxial flexural strength test using the Weibull analysis was performed to evaluate the mechanical properties. Scanning electron microscopy, grain size distribution, and average grain size were used to analyze the microstructures. The TP content of the ZR Lucent ULTRA was the highest among the samples investigated. The Rietveld analysis revealed that the cubic zirconia phase content of the ZR Lucent ULTRA was the highest. The biaxial flexural strength of the ZR Lucent ULTRA was the lowest (622.9 MPa). The average grain size and proportion of large grains (1.0 µm < x) were the highest in ZR Lucent ULTRA. Therefore, extra-high translucent zirconia has the potential for use in anterior monolithic restorations owing to its esthetics and strength.